The rules of living well : a personal code for a healthier, happier you - Templar, Richard, 1950-2006 (Pearson, 2023)
"A personal code for a healthier, happier you. When did life get so busy? Work, family, exercise - they're all important but there's never enough time. How can you effortlessly achieve a healthy balance between them all so you can reach your potential? The Rules of Living Well are here to help. Covering everything from mindfulness, mental health, wellbeing, longevity, energy, balance, perspective, relaxation to exercise, you'll find simple ways to have a healthy attitude and be your best self. What are you waiting for?